Influence of NiO decoration on adsorption capabilities of black phosphorus monolayer toward nitrogen dioxide: periodic DFT calculations. Issue 14 (21st September 2020) - Ghadiri, Mahdi; Ghashghaee, Mohammad; Ghambarian, Mehdi
ABSTRACT: This paper deals with the influence of NiO decoration of black phosphorene (BP) monolayer with respect to nitrogen dioxide (NO2 ) capture and monitoring. The most stable configuration in the adsorption adduct with the modified surface (NP) was slightly different with a shorter equilibrium distance. The modification was found to be highly favourable (−112.60 kcal/mol at HSE06/TZVP). The detection efficiency, defined here as the work function sensitivity, was enhanced by 60% after the NiO modification. While the decorated slab was a disposable sensor at room temperature, it could be an excellent reusable sensor at high temperatures (above 673 K). Moreover, the NP material displayed stronger adsorption (by a factor of 116) compared to the pristine surface, thus making the modified material an excellent candidate for NO2 capture and catalysis. The observed behaviours were discussed in terms of the electronic properties, reactivity indicators, orbital distributions, charge density difference, and density of states.